Civilization Lost and Re-discovered, International Efforts for Advocacy and Conservation of Ani Archaeological Site - Chao, Hunghsi; Bell, Jonathan S. (Restauro Archeologico, 2023)
Located in modern-day eastern Türkiye, Ani was the ancient capital of the prosperous Armenian Bagratid period in the Middle Ages renowned as the “City of 1,001 Churches”. Unfortunately, due to a series of massive earthquakes, shifting trade routes and periodic conflict, Ani’s great buildings were abandoned before the 17th century, leaving the expansive ruins of the city unattended and exposed to the elements. World Monuments Fund (WMF) has maintained a presence at the site in Kars Province, Türkiye since its inclusion on the 1996 World Monuments Watch, which raised international awareness of the need for protection of this significant built fabric. The decades-long project has integrated professionals from Türkiye, Armenia, Iran, Russia and the United States, making the preservation of Ani a truly international endeavor and establishing a model for project-focused international collaboration. This paper sets forth some of the key considerations and components in the establishment of a collaborative preservation that facilitates regional coordination, international cooperation, and global cultural exchange.